Behavioral Consumption of Food Consumption in Adiwiyata High School Students in Mojokerto Regency - Sari, Niki Laila; Haryono, Agung; Sunaryanto, Sunaryanto (STAI Nurul Islam Mojokerto, 2024)
This study aims to examine the behavior of environmentally friendly food consumption in high school students Adiwiyata in Mojokerto Regency. The sub focus of this research is the reasons that underlie students to behave in environmentally friendly food consumption, behavior in environmentally friendly food consumption, environmental education in behaving environmentally friendly food consumption, barriers in behaving in environmentally friendly food consumption. This research method uses qualitative case study type with a multi-case design. The results of this study are health and the environment as a fundamental reason for students in behaving environmentally friendly food consumption, high school students Mojokerto Regency has not behaved maximally environmentally friendly food consumption, environmental economic education has not been carried out optimally in the behavior of environmentally conscious food consumption of students in schools , food sold in schools is a major factor inhibiting students in behaving environmentally friendly food consumption. The suggestions in this study are for students to have awareness of consumption behavior and responsibility, for principals to be more assertive in implementing regulations on the use of plastics and provide support so that students behave in environmentally friendly food consumption, for researchers to further develop research on food consumption behavior from the perspective another.